Our First experience of Using Biodegradable Implants in Latarjet – Bristow Surgical Procedure at Chronic Posttraumatic Anterior Shoulder Insta - V. A. Monastyrev; M. E. Puseva; N. S. Ponomarenko (Acta Biomedica Scientifica)
Background. Multi-layer spiral computed tomography shows that the main cause of shoulder instability is glenoid cavity bone defect. The aim of our research was to assess the effectiveness and safety of biodegradable implants in the treatment of patients with chronic posttraumatic anterior shoulder instability under conditions of bone defect of glenoid cavity margin by the restoration of anatomic shape and structure of scapula articular surface.Materials and methods. We performed a pilot study based on the results of surgical treatment of 7 patients using 4.5 mm biodegradable compressing screws. In preoperative period, all patients had standard two-dimensional X-rays and MSCT with 3D-reconstruction. In postoperative period, all patients had check-up X-ray right after the surgery and MRI in 3 months after the surgery.Results. The results of the treatment were assessed by common clinical criteria, functional criteria, X-ray evidence and intraand postoperative complications. We registered strong functioning of an arm and an increase in the range of motions. Data from Rowe/Zarins and DASH questionnaires showed that the patients totally recovered. X-ray evidence showed consolidation of non-free autograft to the zone of scapula bone defect without osteolysis or widening of a drilled hole. We did not observe either a failure of union, or any formation of false joint, or any screw fractures in bone tissue. Beyond that, we did not observe any complication in postoperative period and early postoperative complications in particular.Conclusion. Pilot study with use of modern biodegradable implants in osteoplastic stabilization of shoulder joint at recurring instability showed their effectiveness and safety in patients of young and active working age. However, considering small number of patients in pilot study we cannot extrapolate our results to all similar and analogue cases of using biodegradable implants. In this regard, it is necessary to perform major multicenter clinical randomized study for further long-term observation and detection of possible unwanted side effects.